Crystal structure of 3-(E)-benzylidene-(1RS,2SR,5RS,6SR)-tricyclo[4.2.2.0 2,5]deca-7-ene-9,9,10,10-tetracarbonitrile, C21H 14N4 - Gream, G.E. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures